Deciphering the roles of myeloid derived suppressor cells in viral oncogenesis - Glover, Alexander; Zhang, Zhaoqin; Shannon-Lowe, Claire (Frontiers in Immunology, 2023)
Myeloid derived suppressor cells (MDSCs) are a heterogenous population of myeloid cells derived from monocyte and granulocyte precursors. They are pathologically expanded in conditions of ongoing inflammation where they function to suppress both innate and adaptive immunity. They are subdivided into three distinct subsets: monocytic (M-) MDSC, polymorphonuclear (or neutrophilic) (PMN-) MDSC and early-stage (e-) MDSC that may exhibit differential function in different pathological scenarios. However, in cancer they are associated with inhibition of the anti-tumour immune response and are universally associated with a poor prognosis. Seven human viruses classified as Group I carcinogenic agents are jointly responsible for nearly one fifth of all human cancers. These viruses represent a large diversity of species, including DNA, RNA and retroviridae. They include the human gammaherpesviruses (Epstein Barr virus (EBV) and Kaposi’s sarcoma-Associated Herpesvirus (KSHV), members of the high risk human papillomaviruses (HPVs), hepatitis B and C (HBV, HCV), Human T cell leukaemia virus (HTLV-1) and Merkel cell polyomavirus (MCPyV). Each of these viruses encode an array of different oncogenes that perturb numerous cellular pathways that ultimately, over time, lead to cancer. A prerequisite for oncogenesis is therefore establishment of chronic infection whereby the virus persists in the host cells without being eradicated by the antiviral immune response. Although some of the viruses can directly modulate the immune response to enable persistence, a growing body of evidence suggests the immune microenvironment is modulated by expansions of MDSCs, driven by viral persistence and oncogenesis. It is likely these MDSCs play a role in loss of immune recognition and function and it is therefore essential to understand their phenotype and function, particularly given the increasing importance of immunotherapy in the modern arsenal of anti-cancer therapies. This review will discuss the role of MDSCs in viral oncogenesis. In particular we will focus upon the mechanisms thought to drive the MDSC expansions, the subsets expanded and their impact upon the immune microenvironment. Importantly we will explore how MDSCs may modulate current immunotherapies and their impact upon the success of future immune-based therapies.